320 Study design and interim recruitment into the post-authorization safety study to monitor pregnancy and infant outcomes following administration of dupilumab during planned or unexpected pregnancy in North America. (25th January 2023) - Johnson, Diana L; Xu, Ronghui; Luo Y, Yunjun; Jones, Kenneth Lyons; Chambers, Christina D; ,
Abstract: Dupilumab is a recombinant human immunoglobulin G (IgG) 4 monoclonal antibody that inhibits interleukin-4 and interleukin 13 signallings. Dupilumab has been approved in the United States (US) and Canada for the treatment of moderate-to-severe atopic dermatitis (AD), moderate-to-severe asthma and chronic rhinosinusitis with nasal polyps, and additionally in the US for eosinophilic esophagitis and prurigo nodularis. Data on the safety of dupilumab exposure during pregnancy is limited. This is a North American-based registry study designed to monitor pregnancy and infant outcomes among women in the US and Canada exposed to dupilumab when used to treat moderate-to-severe AD and moderate-to-severe asthma. The primary data collected from this prospective post-marketing pregnancy registry will allow for a better understanding of any effects of dupilumab exposure on pregnancy and infant outcomes in a real-life clinical setting. Presented is an overview of the study design and interim recruitment into this pregnancy study. The study will assess the risks of major structural birth defects, spontaneous abortion, elective termination, stillbirth, preterm delivery, the pattern of three or more minor structural defects, small for gestational age, postnatal growth at approximately 1 year of age, and serious or opportunistic infections in the first year of life in pregnancies exposed to dupilumab compared to a disease-matched comparison (DC) group and a healthy comparison (HC) group. This OTIS research study is a North American, prospective cohort study comparing pregnancy outcomes in participants exposed to dupilumab for asthma and/or atopic dermatitis to a DC group with asthma and/or atopic dermatitis without dupilumab exposure, and to an HC group. Participants exposed to dupilumab during pregnancy who do not meet the eligibility criteria are enrolled into a 'case series' and these data may be used to further inform on the safety of dupilumab. Recruitment began in October 2018 and will continue through October 2023, with a goal of 500 participants in the cohort study (200 dupilumab-exposed, 200 DC and 100 HC). The study captures data on exposures, outcomes and covariates through maternal interviews and maternal and pediatric medical records, and a pediatric dysmorphology exam. Disease severity is measured by maternal questionnaires and patient-reported disease severity scales. Between 24 October 2018 and 1 November 2022, 354 participants were enrolled in the cohort study, 144 Dupilumab-exposed, 134 DC and 76 HC. An additional 28 participants were enrolled in the dupilumab case series group. The most common reason for enrollment into the case series was retrospective enrollment, followed by having an indication other than AD or asthma and having exposure prior to the last menstrual period. The publication of this data will help healthcare professionals and their patients make informed treatment decisions during pregnancy.